The Effect of Using Offline Web-Based Interactive Multimedia on Students' Biology Learning Outcomes - Rosana Rosana; Abu Darda; Zaenudin Zaenudin (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the effect of offline web-based interactive multimedia on students' biology learning outcomes in the human and ruminant digestive systems. The study also aims to compare the effectiveness of this media with conventional learning media in the form of presentation slides. Methodology: The study used a quasi-experimental method with a two-group pretest-posttest design. The sample was selected using cluster random sampling. The research instrument was a multiple-choice biology learning outcome test. Data analysis used the Chi-square test, Fisher's exact test, and the t-test. Data processing was performed using Microsoft Excel and the Statistical Package for the Social Sciences software. Main Findings: The results showed that the pretest and posttest data were normally distributed and homogeneous. There was no significant difference in pretest scores between the experimental and control groups. There was a significant difference in posttest scores between the two groups. The group using offline web-based interactive multimedia achieved higher learning outcomes than the group using presentation slides. This medium has been proven effective in improving students' biology learning outcomes. Novelty/Originality of this study: The novelty of this research lies in the application of offline web-based interactive multimedia to biology learning, specifically the concept of the human and ruminant digestive systems. This research provides an innovative alternative digital learning media that can be used without an internet connection, thereby expanding the use of educational technology and adding empirical references regarding the effectiveness of interactive media in improving student learning outcomes.